2023
DOI: 10.3390/su15032448
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Short Video Platform Characteristics on Users’ Willingness to Share Marketing Information: Based on the SOR Model

Abstract: User marketing information sharing plays a significant role in boosting the effectiveness of short video marketing. Exploring the factors influencing the willingness to share has become a meaningful way to improve the dissemination of marketing information. This study examines how the characteristics of short video platforms affect users’ willingness to share marketing information and investigates the mediating role of users’ flow experience. We adopted qualitative and quantitative analyses to explore the issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…, 2022; Hsu et al. , 2012; Shi et al. , 2023) affirmed the essential role of ISS in predicting organisms and responses in the S-O-R model.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…, 2022; Hsu et al. , 2012; Shi et al. , 2023) affirmed the essential role of ISS in predicting organisms and responses in the S-O-R model.…”
Section: Introductionmentioning
confidence: 80%
“…Past studies (e.g. Elsotouhy et al, 2022;Hsu et al, 2012;Shi et al, 2023) affirmed the essential role of ISS in predicting organisms and responses in the S-O-R model. In addition, Ali et al (2021) argued that the revised ISS model developed by Delone and Mclean (2003) is appropriate for forecasting user engagement, a stimulus in the current study, with smartphone apps such as m-payment apps.…”
Section: Introductionmentioning
confidence: 95%
“…Perceived value and consumer satisfaction significantly influenced consumer behavior, underscoring the study’s significance in enhancing airport services. Shi et al (2023) contended that establishing a SOR model for live-streamed short videos helped assess user willingness to share marketing information on short video platforms. Their findings highlighted the substantial influence of information quality on user willingness to share marketing information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hausman and Siekpe [5] have shown that flow can affect online consumers' purchase and return intentions. Shi et al [6] examined the effect of flow experience on information sharing intention in short video platforms. This study explores the influence of flow experience on users' visual behavior from the perspective of visual complexity.…”
Section: Introductionmentioning
confidence: 99%